Insights: themes in literature - Carlsen, G. Robert, 1917-; Tovatt, Anthony (New York, Webster Division, McGraw-Hill, 1967)
A thematically arranged anthology of poems, short stories, plays, and novellas for the ninth-grade reader.
Keywords: Children's literature; Comparative literature -- Themes, motives; Literature -- Collections